(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
Globally, the backward extrusion process plays a significant role in manufacturing industries. When designing forming processes, manufacturing engineers can use Finite Element (FE) simulations of backward extrusion, which replace expensive press-shop try-outs with a computer-aided design environment. This paper’s primary goal is to create a numerical model that can accurately replicate the reverse extrusion process. Finite Element software ANSYS will be used to predict billet behavior during the backward extrusion process, helping to eliminate trial-and-error procedures and thus shorten development phases when tight time-to-market deadlines are required. The simulation and analysis of a number of important backward extrusion process parameters, including forming force, stress, and strain distribution in a billet, are the main objectives of this work. A commercial Al-Mg-Si alloy (6082) is used in this study. Experimental results demonstrate the effectiveness of FE simulations, with a strong focus on backward extrusion production. There is a good agreement between the forming load values obtained from the finite element simulation and the experimental procedure.